Criteria for Selecting a Life Partner among Muslim Adolescents: A Mixed Methods Analysis - Johar, Rama Dhini Permasari; Yulisa, Ike; Minal, Fhuja Putri Okta (International Journal of Islamic Studies Higher Education, 2024)
One of the challenges faced by Muslim teenagers today is the advancement of time and technology, which also affects changes in people's mindset and behavior. This study aims to analyze the mindset of Muslim teenagers in choosing life partner criteria in the modern era. The method used in this research is mixed methods design with concurrent embedded strategy model. The research informants consisted of sixteen santri in one of the Islamic boarding schools in West Sumatra, Indonesia, in 2024, who were selected using purposive sampling method. Data were collected through in-depth interviews and questionnaires. Data analysis was conducted through the stages of data reduction, presentation, and verification. The results of qualitative data analysis were combined with the results of quantitative data analysis to produce more in-depth findings. The results showed that religious factors are the main consideration in choosing a life partner for students of Islamic boarding schools, with various supporting reasons. The second dominant factor is employment, followed by fertility factors and the status of a girl or virgin.